2023
DOI: 10.1186/s13287-023-03370-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy in end-stage liver disease: replace and remodel

Abstract: Liver disease is prevalent worldwide. When it reaches the end stage, mortality rises to 50% or more. Although liver transplantation has emerged as the most efficient treatment for end-stage liver disease, its application has been limited by the scarcity of donor livers. The lack of acceptable donor organs implies that patients are at high risk while waiting for suitable livers. In this scenario, cell therapy has emerged as a promising treatment approach. Most of the time, transplanted cells can replace host he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 213 publications
0
8
0
Order By: Relevance
“…In situ analysis showed that the liver was the major organ of small-EVs(<100 nm) localization in the first hour after administration, while distribution to the lungs and spleen peaked between 2 and 12 h. Large-EVs (>200 nm) were most abundant in the lungs in the first hour, followed by a decrease in the lung and an increase in the liver between 2 and 12 h ( Wiklander et al, 2015 ; Morishita et al, 2017 ; Kang et al, 2021 ). Such an accumulation in the liver may be determined by the liver’s physiological characteristics and the immune system’s response ( Hu et al, 2023 ). The liver is characterized by large volume, high vascularity, and high metabolism, which means that EV has a higher chance of being absorbed by the liver through blood circulation ( Yang et al, 2021 ).…”
Section: In Vivo Fates Of Msc-evmentioning
confidence: 99%
See 3 more Smart Citations
“…In situ analysis showed that the liver was the major organ of small-EVs(<100 nm) localization in the first hour after administration, while distribution to the lungs and spleen peaked between 2 and 12 h. Large-EVs (>200 nm) were most abundant in the lungs in the first hour, followed by a decrease in the lung and an increase in the liver between 2 and 12 h ( Wiklander et al, 2015 ; Morishita et al, 2017 ; Kang et al, 2021 ). Such an accumulation in the liver may be determined by the liver’s physiological characteristics and the immune system’s response ( Hu et al, 2023 ). The liver is characterized by large volume, high vascularity, and high metabolism, which means that EV has a higher chance of being absorbed by the liver through blood circulation ( Yang et al, 2021 ).…”
Section: In Vivo Fates Of Msc-evmentioning
confidence: 99%
“…Therefore, prolonging the half-life of MSC-EV is also crucial for improving the rotation rate of MSC-EV. Current strategies can be largely grouped into three main categories: approaches that focus on ( Hu et al, 2023 ) modifying the surface molecules of MSC-EV to improve its liver targeting and evade capture by the immune system ( Yang et al, 2021 ), encapsulating MSC-EV in biomaterials to improve the half-life of MSC-EV, and ( Bruno et al, 2021 ) selecting appropriate delivery strategies to reduce the in vivo pathway of MSC-EV in non-target tissues.…”
Section: Strategies To Improve the Therapeutic Potential Of Msc-evmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, MSCs are utilized to improve liver function while waiting for liver transplantation and can also be used as a potential alternative therapy to organ or hepatocyte transplantation ( 10 ). Some recent clinical trials have reported that infusion of MSCs could induce tolerance after liver transplantation to reduce immune rejection due to the low immunogenicity and immunosuppression of MSCs ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%